(untitled) (American Journal of Medical Science and Innovation, 2025)
Uterine fibroids (leiomyomas) are benign tumors of the uterus, commonly present among women of reproductive age, affecting fertility outcomes. This systematic review aims to gather the current evidence regarding the association between fibroids and subfertility. Additionally, this review aims to analyze national recommendations to conclude the best uterine fibroid treatment, while highlighting the optimal method of enhancing pregnancy rates. A thorough literature search was conducted to retrieve standard of practice guidelines across PubMed, Google Scholar, and MEDLINE databases. Further guidelines were also searched through relevant websites of obstetrics and gynecology associations. Hence, seven international clinical guidelines were retrieved. The findings state that fibroids can affect fertility through several mechanisms, such as modification of the uterine environment, and distortion of fallopian tubes and uterine cavity, leading to potential implantation and placentation failure. In addition, various fibroid management approaches, including medical treatments like surgical and minimally invasive interventions in women desiring future fertility, are investigated. Latest studies suggest that the amount, size, and location of fibroids impact fertility outcomes. All guidelines recommend that during the selection of a treatment method, personalized patient requirements like the preference for childbirth in the future should be taken into consideration. The number, size, and location of fibroids are critical elements to take into consideration. Globally, fibroid management with inexplicable infertility in women has limited empirical and standardized guidelines. Therefore, further research is crucial to understand the fundamental mechanisms and to establish effective management strategies for women with fibroids facing subfertility.